2020
DOI: 10.1097/sih.0000000000000446
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Self-efficacy and Performance of Simulated Neonatal Chest Compressions and Ventilation

Abstract: Introduction Because improved competence in caring for patients is difficult to measure, self-efficacy (the strength of one's belief in one's ability to complete a task) is often used as a surrogate measurement of clinical ability. However, studies in adults and children have shown at best only weak correlations between self-efficacy and performance. This correlation has not been well studied in neonatal resuscitation limiting the utility of self-efficacy as a measurement of the effectiveness of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…La mayor parte de la literatura menciona que implementar la simulación como parte del proceso de aprendizaje, permite favorecer y mejorar la autoeficacia (14,15,16,17) , otros en cambio no han encontrado una correlación directa (18) . Sin embargo, cuando un equipo docente diseña las actividades que el estudiantado debe realizar para cumplir con ciertos resultados de aprendizaje e indicadores, se crean ambientes simulados que reproducen situaciones que favorecen la enseñanza de procedimientos tanto de diagnóstico como terapéuticos, facilitando la repetición de procesos o de situaciones clínicas que promuevan la toma de decisiones profesionales (19) .…”
Section: Discussionunclassified
“…La mayor parte de la literatura menciona que implementar la simulación como parte del proceso de aprendizaje, permite favorecer y mejorar la autoeficacia (14,15,16,17) , otros en cambio no han encontrado una correlación directa (18) . Sin embargo, cuando un equipo docente diseña las actividades que el estudiantado debe realizar para cumplir con ciertos resultados de aprendizaje e indicadores, se crean ambientes simulados que reproducen situaciones que favorecen la enseñanza de procedimientos tanto de diagnóstico como terapéuticos, facilitando la repetición de procesos o de situaciones clínicas que promuevan la toma de decisiones profesionales (19) .…”
Section: Discussionunclassified
“…Individuals in the physician group may have been involved with more high-risk resuscitations over their lifetimes and this may have influenced the lack of change in confidence. Increased experience is associated with higher baseline confidence in resuscitation [18] and prior experience with a medical procedure is associated with increased confidence in performing it [19]. Another factor for differences in confidence may be related to gender as multiple studies have shown women perceive themselves as less self-confident in many areas of medicine [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, teams in our study of debriefings seemed to focus more on CRM‐related concerns than on the medical management of PALS, but the study was not designed to correlate their qualitative discussions of performance with other parameters, such as quantitative measures of CPR quality. Within the resuscitation education literature, there is a growing awareness that reported self‐efficacy for clinical skills is not an adequate indicator of performance in real‐life emergencies 25,26 . It may be that future studies of clinical event debriefing can help address possible gaps between perception and reality regarding resuscitation performance in cardiac arrests and other high‐stakes events.…”
Section: Discussionmentioning
confidence: 99%